Climate Change and Its Effect on Temperature and Precipitation Trends: Case Study in Surabaya Using RegCM5 - Asyam Mulayyan Dary; Mas Agus Mardyanto; Joni Hermana; Chairul Imron ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
Climate change is increasingly driving extreme weather events, yet its regional impacts remain complex. This study employs the RegCM5 model, driven by ERA5 reanalysis data, to simulate high-resolution (5 km) climate dynamics in Surabaya, Indonesia from December 2018 to November 2023. Validated against gridded observational datasets and analyzed via Earth's energy balance, the results reveal a steady rise in both top-of-atmosphere and surface energy imbalances, corresponding with record-breaking increases in maximum and minimum temperatures by approximately 1.5°C and 1°C from 2020 to 2023. While monthly precipitation patterns were inconsistent, daily observations indicate a significant increase in high-intensity precipitation events. These findings offer critical insights into evolving regional climate impacts and inform local adaptation and mitigation strategies.